Implementation of UINSU Repository System for Publication of Electronic Collections of UIN Sumatera Utara Academic Community - Paris Alvito; Bintang Hutagalung; Sultan Azka El Husein Lubis; Ananda Sarbaini Firin (Switch : Jurnal Sains dan Teknologi Informasi, 2025)
The need for an efficient system to manage academic works in digital format is growing in universities, including at Universitas Islam Negeri Sumatera Utara (UINSU). Despite previous developments in digital repository systems, many academic institutions, including UINSU, still face challenges related to data management, security, and accessibility. This study aims to develop a web-based repository system for UINSU using the Waterfall method, to improve the storage, management, and accessibility of academic resources. A structured quantitative approach was adopted, focusing on the development and implementation of the repository system. The Waterfall methodology was chosen due to its step-by-step approach, ensuring a thorough and organized development process. The implementation of the system resulted in an organized, user-friendly platform where students, faculty, and staff can upload, manage, and access academic documents efficiently. The system features a clear interface for searching, uploading, and managing documents, with administrative controls for approving and maintaining submissions. The repository system significantly improves data management at UINSU, providing a long-term solution for archiving academic work. Continuous evaluation and system upgrades are essential to ensure it adapts to future needs and technological advancements.